Renewable Energies and European Landscapes: Lessons from Southern European Cases - Frolova, Marina (Springer, 2015)
This book provides timely, multidisciplinary cross-national comparison of the institutional and social processes through which renewable energy landscapes have emerged in Southern Europe. On the basis of case studies in these countries, it analyzes the way in which and the extent to which the development of renewable energies has affected landscape forms and whether or not it has contributed to a reformulation of landscape practices and values in these countries. Landscape is conceived broadly, as a material, social, political and historical process embedded into the local realm, going beyond aesthetic.